Peru : Staff Report for the 2004 Article IV Consultation, Fourth Review Under the Stand-By Arrangement, and Request for Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Peru's 2004 Article IV Consultation, Fourth Review Under the Stand-By Arrangement, and Request for Waiver of Nonobservance of Performance Criterion. In 2003, Peru's real GDP grew by 4 percent, with inflation of 2.5 percent and a further strengthening of the external position. Fiscal reforms have progressed well over the last two years, including the creation of a sound legal framework for fiscal decentralization, improved fiscal transparency, and further pension reforms. The authorities' economic program for 2004 foresees continued economic growth, based on a further recovery of investment and strong export growth.